Раціональне використання суміщеного методу монтажу конструкцій та технологічного обладнання при зведені промислових об’єктів - Лучинський, С. А. (Ways to Improve Construction Efficiency, 2012)
The paper deals with reducing construction time by combining the installation method of building structures and technological equipment of the site, as well as with current organizational and technological conditions of the construction and management of labor and material costs.